A biological luminescent metal–organic framework with high fluorescence quantum yield for the selective detection of amino acids and monosaccharides. Issue 7 (31st January 2022) - Zhou, Ying-Ying; Xu, Yuan; Yu, Maoxing; Xiong, Yi; Liu, Xun-Gao; Zhao, Zujin
Abstract : A tetraphenylethene-based biological luminescent metal–organic framework with high fluorescence quantum yield is developed for selective and sensitive detection of amino acids and monosaccharides in aqueous medium. Abstract : The biological luminescent metal–organic framework (bio-LMOF), (Me2 NH2 )2 [Zn6 O(Ade)4 (TCPPE)2 ] (1 ) {H4 TCPPE = tetrakis[4-(4-carboxyphenyl)phenyl]ethene, Ade = adenine} was successfully designed and synthesized under hydrothermal conditions, with two channels of different sizes. The absolute fluorescence quantum yields of complex 1 and activated 1 are up to 77.6% and 85.9%, respectively. Activated 1 exhibits outstanding water stability and excellent selective luminescence sensing for amino acids and monosaccharides. The fluorescence quenching efficiencies of activated 1 towards l -Nph and d -Nga are 86.35% and 91.60%, respectively. Besides, activated 1 also displays highly quenching responses to l -Nph and d -Nga at fairly low concentrations, and the limits of detection for l -Nph and d -Nga are estimated to be 0.149 ppm and 1.612 ppm, respectively. Meanwhile, in multiple cycling experiments, activated 1 still has excellent cycling stability. These phenomena indicate that activated 1 can be utilized as a fast responsive biological luminescent sensor, which is a rare example for bio-LMOFs.